2013
DOI: 10.1021/nn403788a
|View full text |Cite
|
Sign up to set email alerts
|

Design of Pt-Shell Nanoparticles with Alloy Cores for the Oxygen Reduction Reaction

Abstract: We report that the oxygen binding energy of alloy-core@Pt nanoparticles can be linearly tuned by varying the alloy-core composition. Using this tuning mechanism, we are able to predict optimal compositions for different alloy-core@Pt nanoparticles. Subsequent electrochemical measurements of ORR activities of AuPd@Pt dendrimer-encapsulated nanoparticles (DENs) are in a good agreement with the theoretical prediction that the peak of activity is achieved for a 28% Au/72% Pd alloy core supporting a Pt shell. Impor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
147
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(155 citation statements)
references
References 26 publications
7
147
1
Order By: Relevance
“…Comparing E seg (Pt) along x axis, only Au has a positive E seg (Pt) and is preferentially located on the surface forming Pt@Au (1.13 eV) while others, Co (-2.39 eV), Cu (-1.33 eV) and Pd (-0.16 eV), will reside in the subsurface forming M@Pt. This result, in consistent with previous experimental 4, 6, 32, 45 and computational28,[47][48] studies, can be attributable to the radius of M that larger (Au) and smaller (Co, Cu, Pd) M will expand and reduce, respectively, Pt lattice and are thermodynamically stable on the surface and in the subsurface, respectively, to minimize the stress upon alloying.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…Comparing E seg (Pt) along x axis, only Au has a positive E seg (Pt) and is preferentially located on the surface forming Pt@Au (1.13 eV) while others, Co (-2.39 eV), Cu (-1.33 eV) and Pd (-0.16 eV), will reside in the subsurface forming M@Pt. This result, in consistent with previous experimental 4, 6, 32, 45 and computational28,[47][48] studies, can be attributable to the radius of M that larger (Au) and smaller (Co, Cu, Pd) M will expand and reduce, respectively, Pt lattice and are thermodynamically stable on the surface and in the subsurface, respectively, to minimize the stress upon alloying.…”
supporting
confidence: 91%
“…The concept has also been confirmed from the density functional theory (DFT) computational studies. [17][18][19][20][21][22][23][24][25][26][27][28][29]. al.…”
Section: Introductionmentioning
confidence: 99%
“…The spectrum obtained using He + ions is presented in Fig. 21 At the same time, ClO 4 − anions are only weakly adsorbed on Pt(111) making this surface more active than Pt (100). Three intense features are observed which correspond to carbon (∼42 kV), Ru (∼74 kV), and Pt (∼77 kV).…”
Section: Resultsmentioning
confidence: 97%
“…For example, Zhang et al [443] reported that the ORR activities of PdAu@Pt can be linearly tuned through varying the alloy core composition and that optimal activities can be achieved with a 28% Au/72% Pd alloy core supporting a Pt shell. Alloy cores composed of other precious metals have also been reported, such as PdAu@Pt [288] and PdPt@Pt [148,150,151,444].…”
Section: Au As Corementioning
confidence: 99%